PENGARUH SENAM ERGONOMIK TERHADAP PENURUNAN KADAR GULA DARAH PADA LANSIA DENGAN DIABETES MELITUS DI DESA SIDAKARYA, DENPASAR SELATAN - Febrianti, Ni Putu Mira; Wijaya, I Putu Artha; Kio, Alfiery Leda (Poltekkes Kemenkes Medan, 2021)
Diabetes mellitus is a chronic metabolic disorder caused by pancreas that does not produce enough insulin, resulting on the inability of the body to use insulin effectively. The symptoms suffered by patients are often mild and this causes considerable people with diabetes mellitus do not realize that they have diabetes mellitus. If Diabetes Mellitus is not immediately treated, it would cause long-term complication including macrovascular diseases. Plentiful elderly with Diabetes Mellitus in Sidakarya Village do not realize that they suffer from Diabetes Mellitus and prefer to do non-pharmacological therapy. One of non-pharmacological therapies that can reduce blood sugar levels is ergonomic exercises. The aim of this study was to find out how ergonomic exercises effected towards the lower of blood sugar levels in elderly in Sidakarya Village, South Denpasar. This study is a quantitative research using Pre-Experimental Design One Group Pre-Test Post-Test with total samples of 19 elderly. Data was analysed using non-parametric test of Wilcoxon Sign Rank Test in order to compare the result of the pre-test and post-test. The result of this study showed that prior to the implementation of ergonomic exercises, it was found approximately 57,9% respondents who suffered from prediabetes and 42,1% respondents who suffered from diabetes, while after intervention of ergonomic exercises were given, there were only 7 respondents (36,8%) who suffered from diabetes and 12 respondents (63,2%) who have normal blood sugar levels. According to the calculation result, it was obtained that p value = 0,0001 < ? 0,05 and Zcount -3.824b that showed an effect of ergonomic exercises towards the lower of blood sugar levels in elderly in Sidakarya Village, South Denpasar. Based on the result of this study, ergonomic exercises is expected to be able to help reducing blood sugar levels in elderly with Diabetes Mellitus who prefer to do non-pharmacological therapy.